Brucella Antibodies in Alaskan True Seals and Eared Seals—Two Different Stories - Nymo, Ingebjørg H.; Rødven, Rolf; Beckmen, Kimberlee; Larsen, Anett K.; Tryland, Morten; Quakenbush, Lori; Godfroid, Jacques (Frontiers in Veterinary Science, 2018)
Brucella pinnipedialis was first isolated from true seals in 1994 and from eared seals in 2008. Although few pathological findings have been associated with infection in true seals, reproductive pathology including abortions, and the isolation of the zoonotic strain type 27 have been documented in eared seals. In this study, a Brucella ELISA and the Rose Bengal Test (RBT) were initially compared for 206 serum samples and a discrepancy between the tests was found. Following removal of lipids from the serum samples ELISA-results were unaltered while the agreement between the tests was improved, indicating that serum lipids affected the initial RBT-outcome. For the remaining screening we used ELISA to investigate the presence of Brucella antibodies in sera of 231 eared and 1412 true seals from Alaskan waters sampled between 1975 and 2011. In eared seals, Brucella antibodies were found in two Steller sea lions (Eumetopias jubatus) (2 %) and none of the 107 Northern fur seals (Callorhinus ursinus). The low seroprevalence in eared seals indicate a low level of exposure or lack of susceptibility to infection. Alternatively, mortality due to the Brucella-infection may remove seropositive animals from the population. Brucella antibodies were detected in all true seal species investigated; harbor seals (Phoca vitulina) (25 %), spotted seals (Phoca larga) (19 %), ribbon seals (Histriophoca fasciata) (16 %) and ringed seals (Pusa hispida hispida) (14 %). There was a low seroprevalence among pups, a higher seroprevalence among juveniles, and a subsequent decreasing probability of seropositivity with age in harbor seals. Similar patterns were present for the other true seal species, however, solid conclusions could not be made due to sample size. This pattern is in accordance with previous reports on B. pinnipedialis-infections in true seals and may suggest environmental exposure to B. pinnipedialis at the juvenile stage, with a following clearance of infection. Furthermore, analyses by region showed minor differences in the probability of being seropositive for harbor seals from different regions regardless of the local seal population trend, signifying that the Brucella-infection may not cause significant mortality in these populations. In conclusion, the Brucella infection pattern is very different for